Role of ethical organisational culture on employee job satisfaction: an empirical study. (6th April 2022) - Joseph, Shaji; Jadhav, Anil; Vispute, Bhamini
The aim of this study is to understand impact of ethical culture of information technology (IT) organisation on employee job satisfaction. In this study, we have identified the constructs of ethical culture of IT organisations on the basis of review of literature and proposed a model indicating the relationship between the identified constructs and job satisfaction. The study is done especially for employees of IT organisations in Pune, India, based on a survey of 124 employees working in IT firms. We have analysed the impact of organisations' ethical culture constructs namely equal opportunity, fairness in promotion process, impartiality in grievance handling, ethical leadership, and ethical policy on employee job satisfaction. Results of the analysis revealed that ethical policy, impartiality in grievance handling, and fairness in promotion process have significant impact on job satisfaction of the employees, whereas equal opportunity and ethical leadership has no significant impact on job satisfaction of employees.